Alleviation of Lead Toxicity by 5-Aminolevulinic Acid Is Related to Elevated Growth, Photosynthesis, and Suppressed Ultrastructural Damages in Oilseed Rape. (10th February 2014) - Tian, Tian; Ali, Basharat; Qin, Yebo; Malik, Zaffar; Gill, Rafaqat A.; Ali, Shafaqat; Zhou, Weijun
Abstract : Lead (Pb) is a widely spread pollutant and leads to diverse morphological and structural changes in the plants. In this study, alleviating role of 5-aminolevulinic acid (ALA) in oilseed rape ( Brassica napus L.) was investigated with or without foliar application of ALA (25 mg L −1 ) in hydroponic environment under different Pb levels (0, 100, and 400 µM). Outcomes stated that plant morphology and photosynthetic attributes were reduced under the application of Pb alone. However, ALA application significantly increased the plant growth and photosynthetic parameters under Pb toxicity. Moreover, ALA also lowered the Pb concentration in shoots and roots under Pb toxicity. The microscopic studies depicted that exogenously applied ALA ameliorated the Pb stress and significantly improved the cell ultrastructures. After application of ALA under Pb stress, mesophyll cell had well-developed nucleus and chloroplast having a number of starch granules. Moreover, micrographs illustrated that root tip cell contained well-developed nucleus, a number of mitochondria, and golgi bodies. These results proposed that under 15-day Pb-induced stress, ALA improved the plant growth, chlorophyll content, photosynthetic parameters, and ultrastructural modifications in leaf mesophyll and root tip cells of the B. napus plants.